Kajian kulit kayu Tekalong diaplikasikan dalam rekaan Couture - Emily Evelyn, Roipin. (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study were focuses on experimentation of Tekalong's skin to enhance its characteristic. It is also covers the textures, durability and application to create a surface design using textile techniques